Malaria: methods and protocols - Ménard, Robert (Methods in molecular biology, 2013)
Over the past ten years, many powerful new techniques have been developed that have dramatically changed malaria research. The second edition of Malaria: Methods and Protocols expands upon the previous edition with current, detailed techniques for laboratory research. With new chapters on parasite culture techniques, genome manipulation methods, "omic" approaches, and techniques for studying the biology of the red blood cell and pre-erythrocytic stages of Plasmodium. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Malaria: Methods and Protocols, Second Edition offers a comprehensive set of standard techniques for laboratory researchers.
Keywords: Malaria